Education solutions for child poverty: New modalities from New Zealand. (April 2015) - Airini,
This article describes education solutions to child poverty. Through a focus on New Zealand, the article explores the meaning of child poverty, children's perspectives on child poverty and solutions, and modalities in citizenship, social and economics education to help address child poverty. Four modalities are proposed: centre our work in citizenship, social and economics education on children; explicitly address indigenous peoples' needs and strengths; take a social investment approach; and commit to community-based solutions. Experts in citizenship, social and economics education are encouraged to use the resources available to create solutions to child poverty by changing policies and norms through new modalities.